The Role Of Sensory Marketing In Influencing The Impulse Purchase Decision Of Cosmetic Consumers - نصّور, ريزان (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to identify the concept of sensory marketing and its importance and the definition of the concept of impulse purchase decision, as well as to analyze the impact of sensory marketing on the impulse purchase decision among consumers. To achieve this, the researcher conducted a survey on consumers of Seif beauty clinic in Lattakia governorate. The study reached a set of results, the most important of which was the existence of a significant relationship between sensory marketing on the one hand and personal, external and circumstantial factors affecting the impulsive buying decision among consumers of Seif beauty clinic products and preparations: The research also presented a set of proposals and recommendations that could help companies specialized in marketing such products to understand how to influence the consumer's buying decision, especially (impulse buying).